Mathematical and software tools for modeling objects with distributed parameters - Veremchuk, Andriy; Pukas, Andriy; Voytyuk, Iryna; Spivak, Iryna (2016 13th International Conference on Modern Problems of Radio Engineering, Telecommunications and Computer Science (TCSET), 2016)
In this paper the software system for constructing the mathematical macromodels for objects with distributed parameters using different methods of structure and parameters identification is considered.